79.1k views
5 votes
Please help answer this

Please help answer this-example-1

2 Answers

3 votes

Answer:

Choice C is correct.(f-g)(x) = -4x²+10x is the answer.

Explanation:

We have given two functions:

f(x) = -x²+6x-1

g(x) = 3x²-4x-1

We have to find (f-g)(x) = ?

(f-g)(x) = f(x) - g(x)

Putting values in above formula we get,

(f-g)(x) =(-x²+6x-1) - ( 3x²-4x-1)

(f-g)(x) = -x²+6x-1-3x²+4x+1

(f-g)(x) = -4x²+10x

User Coffka
by
5.0k points
4 votes

For this case we have that given two functions,
f (x)and
g (x), then
(f-g) (x)is given by:


(f-g) (x) = f (x) -g (x)

So:


f (x) = - x ^ 2 + 6x-1\\g (x) = 3x ^ 2-4x-1

We have to:


(f-g) (x) = - x ^ 2 + 6x-1- (3x ^ 2-4x-1)\\(f-g) (x) = - x ^ 2 + 6x-1-3x ^ 2 + 4x + 1\\(f-g) (x) = - 4x ^ 2 + 10x\\

Answer:


(f-g) (x) = - 4x ^ 2 + 10x

Option C

User DAiMor
by
4.7k points